The end of the road : a Maxie and Stretch mystery - Henry, Sue, 1940-2020- (Henry, Sue, 1940-2020- Maxie and Stretch mysteries., 2009)
Maxie McNabb and her miniature dachshund, Stretch, investigate a murder that shatters the quiet in their hometown of Homer, Alaska.